Navigating the new norm: review of health risks associated with widespread disinfectant and hand sanitizer use - Abdullah, Amira Raudhah; Azmi, Liyana; Aziz, Muhamad Afiq; Abidin, Nur Waliyuddin Hanis Zainal; Jasmiad , Muhammad Idham (International Journal Of Community Medicine And Public Health, 2025)
The COVID-19 pandemic led to increased global use of alcohol-based hand sanitizers (ABHS) and disinfectants as key infection control measures. While initially implemented as emergency measures, their continued and widespread use in healthcare and community settings has raised concerns regarding long-term safety and environmental impact. This systematic review aimed to evaluate the adverse health effects associated with ABHS and disinfectants beyond the pandemic phase. Following PRISMA guidelines, a comprehensive search of PubMed, Google Scholar and Scopus identified studies published between 2014 and 2025. Eleven studies met inclusion criteria, focusing on chemical composition, exposure routes and the toxicological outcomes. Evidence shows that dermal absorption, inhalation, ingestion and ocular contact are the main exposure pathways to ABHS and disinfectant. Meanwhile, reported health effects ranging from mild dermatitis to systemic toxicity. Chemicals such as methanol, quaternary ammonium compounds (QACs) and chlorine-based disinfectants were most often linked to respiratory problems, neurological effects, reproductive risks as well as pose risk as environmental contamination. Children, pregnant women, and healthcare workers were found to be especially vulnerable. Weak regulatory oversight during the pandemic contributed to the circulation of substandard or counterfeit products, adding to the risks. The ongoing high use of ABHS and disinfectants in 2025 underscores the importance of stronger regulations, clearer labelling, better quality control, and continuous public education. Moving forward, safer alternatives and sustainable hygiene practices are needed to maintain effective infection prevention while minimizing risks to health and the environment.